2013
DOI: 10.1080/15374416.2013.814543
|View full text |Cite
|
Sign up to set email alerts
|

The Common Elements of Engagement in Children's Mental Health Services: Which Elements for Which Outcomes?

Abstract: Using the distillation component of the Distillation and Matching Model framework (Chorpita, Daleiden, & Weisz, 2005 ), we examined which engagement practices were associated with three domains of treatment engagement: attendance, adherence, and cognitive preparation (e.g., understanding of, readiness for treatment). Eighty-nine engagement interventions from 40 randomized controlled trials in children' s mental health services were coded according to their engagement practices and outcomes. Analyses examined w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
135
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 163 publications
(141 citation statements)
references
References 70 publications
3
135
0
1
Order By: Relevance
“…Preparing and orienting parents to their child's treatment using psychoeducation strategies can help address parent misconceptions about child MH problems and unrealistic treatment expectations, thereby increasing parent involvement in services. Indeed, a recent study found that engagement interventions that outperformed other engagement interventions on indicators of family engagement utilized psychoeducation as a core element (Becker et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Preparing and orienting parents to their child's treatment using psychoeducation strategies can help address parent misconceptions about child MH problems and unrealistic treatment expectations, thereby increasing parent involvement in services. Indeed, a recent study found that engagement interventions that outperformed other engagement interventions on indicators of family engagement utilized psychoeducation as a core element (Becker et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Psychoeducation can also target misperceptions about care, where the rationale for evidence-based interventions can be provided. Indeed, psychoeducation strategies have resulted in increased knowledge about child MH problems (Brent, Poling, McKain, & Baugher, 1993;Fristad, 2006), increased treatment attendance (Becker et al, 2013;Fristad, 2006), adherence with treatment recommendations (Pavuluri et al, 2004), and cognitive preparation of families entering services (Becker et al, 2013). Although there is evidence that therapists in usual care settings provide psychoeducation strategies to parents in the treatment of child disruptive behavior, they rarely deploy these strategies with sufficient intensity to promote a well-developed understanding of child MH problems and treatments (Garland et al, 2010).…”
mentioning
confidence: 99%
“…In light of this, the comprehensive identification of central processes of engagement in the CIE may serve as a guide for future interventions by (a) helping to target work on specific domains to develop strategies or brief interventions to enhance engagement among particular cultural groups and (b) facilitating cultural adaptations of existing engagement practices or interventions. For example, although psychoeducation about services is recognized as one of the most frequent and successful practices utilized by clinicians to enhance engagement (Becker et al 2015), an initial discussion about psychotherapeutic services may be antithetical to the ethnic minority and immigrant family's conceptualization of their child's distress as not mental health related, but rather physical. Conceptualizations stemming from particular causal beliefs about such issues as imbalance in the body and poor energy flow might shape ethnic minority and immigrant families' preferred healing approach toward, for instance, traditional Chinese medicine, while attempts to engage in a conversation about "mental health" would likely invalidate families' concerns and result in treatment dropout.…”
Section: Discussionmentioning
confidence: 99%
“…Within these domains, empirical literature has assessed, for example, session attendance (Nock and Ferriter 2005), adherence (Garvey et al 2006;Nock and Ferriter 2005), therapeutic alliance (Bordin 1994), and cognitive preparation (Becker et al 2015).…”
Section: Current Conceptualization and Assessment Of Engagementmentioning
confidence: 99%
See 1 more Smart Citation